Analysis Of Competency-Based Learning Objectives In Curriculum 13 And Independent Curriculum - Ibnu Alwi Jarkasih Harahap; Sindi Pramita; Radhinal Abdullah; Siti Halimah (Jurnal Multidisiplin Sahombu, 2025)
In the era of globalization and development fast technology, education expected can prepare generation young For face challenge complex involving change social, economic, and technological. Emphasis on mastery skills practical, appropriate attitude, and ability think critical and creative become very important For ensure graduate of Ready facing the dynamic world of work. Although Lots system education Still focus on mastery material in a way theoretical, approach This often ignored application practical from knowledge learned. Research This use library research methods for collect and analyze data from various source written, with objective For dig essence values education that is relevant in the modern era. The results of the analysis show that flexibility in learning and development teacher professionalism is very important For increase quality education and results Study students, so that graduate of can adapt with Good in environment that continues changed.